Characterization of outer membrane vesicles from Acinetobacter haemolyticus and their role in the dissemination of carbapenem resistance - Elsy Martínez-Gorgonio; Rosa del Carmen Rocha-Gracia; Miguel Castañeda-Lucio; Margarita M. P. Arenas-Hernández; Miguel A. Cevallos; Yolanda Sáenz; Patricia Lozano-Zarain (Medical Microbiology and Immunology, 2026)
Species outside the Acinetobacter calcoaceticus–baumannii (Acb) complex have recently emerged as new clinically relevant carbapenem-resistant pathogens, such as A. haemolyticus . A new mechanism that could contribute to the dissemination of this resistance is the secretion of outer membrane vesicles (OMVs). We investigate OMVs secreted by A. haemolyticus AN54, a Mexican clinical strain carrying a plasmid-borne bla NDM−1 gene and by its plasmid-cured derivative AN54Δe. Active secretion of OMVs formed by a lipid membrane, measuring 10–50 nm in both strains, was observed by TEM. The OMVs from AN54 possess hydrolytic capacity against carbapenem. The OMV protein profile varied depending on the antibiotic concentration during induction, with additional protein bands detected at 8 and 32 µg/ml of antibiotic exposure. Mass spectrometry identified proteins involved in different metabolic pathways and in resistance-related processes. The porins, efflux pumps, and ADC enzyme were more abundant in the OMVs from AN54Δe than in those from AN54 harboring the active NDM-1 enzyme. The OMVs protected the sensitive strains from the same and different genera against the antibiotic action for a limited period. However, the OMVs transferred the bla NDM−1 -carrying plasmid (pAhaeAN54e) only to the AN54Δe strain, conferring permanent resistance to carbapenems. Together, these findings suggest that OMVs can help protect surrounding bacteria from antibiotic action and serve as vehicles for disseminating resistance genes. These results show the importance of studying OMVs as a novel mechanism for the dissemination of antimicrobial resistance.

Revealing the complex nature of Maar–Diatreme Volcanoes: insights from lithofacies analysis of the Cretaceous El Carrizal diatreme, NW Argentina - O. Arenas; W. Báez; M. Arnosio; E. Bustos; M.F. Quiroga; M. Cirer (Journal of Volcanology and Geothermal Research, 2026)

Network topology and structural connectivity of coral reef ecosystem in the Mexican tropical Pacific - Ubaldo Jarquín-Martínez; Andrés López-Pérez; Luis G. Abarca-Arenas; Israel Huesca-Domínguez; Ana María Torres-Huerta; Marco Ortiz; Alma P. Rodríguez-Troncoso; Amílcar Leví Cupul-Magaña; Omar Valencia-Méndez; Cristian M. Galván-Villa; Enrique Godínez-Domínguez; Seim Uriel Keller-Rodríguez; et al. (Food Webs, 2026)

The Arlington study of healthy aging: a multidisciplinary community cohort study of functional decline with age - Delaney L. Davis; Rajvi Shah; Logan Pixler; Dang M. Mai; Juliana Santos; Camille Chandler; Kendall White; Jennifer Nguyen; Ario S. Moradi; Javed Choudhari; Carrie Arena-Marshall; Chase Johnson; et al. (GeroScience, 2026)

Quantifying local wind-mediated dispersal of zooplankton in a Mediterranean pond - Cristina Arenas-Sánchez; Raquel Ortells; María José Carmona; Manuel Serra; Javier Montero-Pau; Eduardo M. García-Roger (Hydrobiologia, 2026)
Dispersal shapes species distributions, population dynamics, and community structure. While zooplankton is assumed to exhibit high dispersal capacity, quantitative data remain scarce, particularly for rotifers. Wind is recognized as an important vector for these organisms at local scales, yet its role in short-distance propagule transport remains poorly quantified. Here, we conducted a 15-month field study in a temporary pond to quantify wind-mediated dispersal of zooplankton propagules. We investigated how wind regime and pond characteristics influence dispersal patterns in rotifers and compared them with those of copepods given their marked differences in propagule size. We also analyzed the relationship between propagule size and dispersal distance. Our findings showed temporal variability and distinct dispersal patterns between the two groups. Wind conditions and pond characteristics were closely associated with patterns of propagule aerial transport. Rotifer dispersal decreased with distance, whereas copepods exhibited the opposite trend, highlighting the complex influence of propagule size on dispersal efficiency. Overall, wind dispersal was highly variable and dependent on changing environmental conditions and propagule availability. This study provides one of the few long-term, field-based quantifications of wind-mediated propagule transport in zooplankton and highlights its relevance at local scales, even during the wet phase of temporary ponds.

Western–Eastern isotopic zonation of the Canary Archipelago reveals spatially organized mantle domains - J. M. Fuenlabrada; E. Ancochea; R. Arenas (Journal of Iberian Geology, 2026)

Phenotypic and genome-wide associations underlying rotifer diapausing egg dispersal - Cristina Arenas-Sánchez; Javier Montero-Pau; Eduardo M. García-Roger; Raquel Ortells; María José Carmona (Hydrobiologia, 2026)
Diapausing eggs are critical for rotifer population persistence and dispersal. Despite their ecological significance, the factors shaping their phenotypic variation and its genetic basis remain largely unexplored. We characterized morphological and biochemical traits related to dispersal in diapausing eggs of two cryptic rotifer species, Brachionus plicatilis and Brachionus rotundiformis, and examined the differences between floating and sinking eggs in B. plicatilis . Additionally, we performed a genome-wide association study in B. plicatilis to identify genetic variants associated with dispersal-related traits. Our analyses revealed pronounced interspecific variation: B. plicatilis produced larger and heavier diapausing eggs, while B. rotundiformis exhibited higher lipid content. Broad-sense heritability indicated stronger genetic control of most traits in B. plicatilis , whereas lipid area showed higher heritability in B. rotundiformis . Differences between floating and sinking eggs in B. plicatilis were linked to lipid content. Floating eggs displayed significantly higher lipid reserves. Genomic analyses identified SNPs significantly associated with embryo area, egg weight, and lipid content, located near genes involved in morphogenesis, embryo development, and a protein family involved in gap junction formation. This work represents one of the first GWAS applications targeting diapausing egg traits in aquatic microinvertebrates and provides insights into the genetic architecture governing dispersal strategies in rotifers.

Consensus on future research directions in the phylum Rotifera - Rafael L. Macêdo; Carlota Solano‐Udina; Melanie D. Borup; Marco Antonio Jiménez‐Santos; Cristina Arenas‐Sánchez; Christina W. C. Branco; Karen Costa; Betina Kozlowsky‐Suzuki; Cláudia C. Bonecker; Elizabeth J. Walsh; André R. S. Garraffoni; S. S. S. Sarma; et al. (Limnology and Oceanography, 2026)
Rotifers play key roles in aquatic ecosystems, yet significant uncertainty remains about their diversity and evolution, and further evidence is needed to determine how reliably their responses to global change and human impacts can inform conservation. To identify major knowledge gaps hindering progress, we carried out a Delphi process both online and during the 17 th International Rotifer Symposium, involving more than 40 experts across diverse regions and subdisciplines. A total of 133 research questions were screened for relevance and clarity and reduced to 100 for online scoring. These were evaluated on a 1‐to‐10 priority scale, after which 67 questions exceeding 50% agreement were advanced to an in‐person workshop. Through structured discussions and round‐table voting, participants identified gold, silver, and bronze priority questions, while considering the feasibility of addressing them, resulting in a final consensus set of high‐priority questions across basic, applied, and philosophical perspectives including how rotifer communities are defined, how evidence is generated and integrated, and how values shape research priorities. Support for questions on knowledge transfer, digital curation, and AI‐assisted identification highlights the emergence of a methodological subfield linking classical approaches with modern computational tools. Likewise, the emphasis on improving genetic markers and connecting DNA sequences with traits shows that molecular research is now viewed as a foundational component of rotiferology. This synthesis provides the first community‐driven roadmap for rotifer research. By articulating shared priorities and clarifying persistent knowledge gaps, including unreliable phylogenies, uneven sampling worldwide, and limited hypothesis‐driven work, it provides a foundation for future collaborative projects, funding strategies, and cross‐disciplinary integration.

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Trace metals enrichments in a pristine hypersaline lagoon as a biosignature of microbial mats applied to modern and ancient sedimentary environments - Jair Carlos Ceja-González; Jacob Alberto Valdivieso-Ojeda; Francisco Delgadillo-Hinojosa; Ronald M. Spelz; Jose de Jesus Paniagua-Michel; Diana Arenas-Islas; Paula Maza-Marquez; Miguel Ángel Huerta-Diaz (Chemical Geology, 2026)

Migration rate, timing of sex, and resident genetic diversity jointly shape effective gene flow during rotifer colonization - Cristina Arenas‐Sánchez; Raquel Ortells; María José Carmona; Eduardo M. García‐Roger; Javier Montero‐Pau (Limnology and Oceanography, 2026)
Dispersal is a complex process that affects all living organisms, with the settlement phase being particularly critical. This phase depends on the interaction between the environmental conditions of the new habitat and the biological traits of both resident and immigrant populations. While these factors have been studied individually, their combined effects remain poorly understood. To address this gap, we conducted a controlled laboratory experiment using populations of the facultatively sexual rotifer Brachionus plicatilis assembled from clonal lines originating from two natural populations—one serving as the resident and the other as the immigrant. We examined how the combination of initial immigrant density, resident population genetic diversity, and the timing of sexual reproduction in immigrants influences effective gene flow. Using genome‐wide single nucleotide polymorphism (SNP) tracking, we quantified the contribution of immigrants to the diapausing‐egg bank. Our results indicate that all three factors—both individually and interactively—significantly affect settlement success. Specifically, higher immigrant density, lower genetic diversity in the resident population, and earlier sexual reproduction in immigrants were all associated with greater effective gene flow. Notably, these factors interacted: high initial density had the strongest impact when combined with early sexual reproduction in immigrants, while low genetic diversity in the resident population facilitated the settlement of immigrants with delayed sexual reproduction. Overall, our results highlight that multiple interacting factors jointly shape colonization outcomes and provide mechanistic insight into how dispersal and reproduction jointly drive gene flow in metapopulations.

Rising herbivory pressure of Sarpa salpa and the emerging threat to Southern European marine forests - J. de Azevedo; J.N. Franco; M. Dolbeth; H.S. Meyer; A. Barreiro; E.A. Salas-Leitón; F. Arenas (Marine Environmental Research, 2026)

Reconstructing volcanic architecture through eruptive style and spatial analysis: Cretaceous rift volcanism in the Alemanía subbasin, Salta, Argentina - M.F. Quiroga; M. Arnosio; E. Bustos; N. Salado Paz; R. Becchio; A. Villagrán; O. Arenas (Journal of South American Earth Sciences, 2026)

Middle Bronze Age axes from the eastern Adriatic: towards the reconstruction of copper supply networks in the 2nd millennium BC - Mario Gavranović; A. Arena; M. Mehofer; N. Mittermair; F. Franković; D. Kliškić; D. Domazet; N. Čondić (Archaeological and Anthropological Sciences, 2026)
This study presents chemical (ED-XRF) and lead isotope (HR-MC-ICP-MS) analyses of 29 bronze axes recovered along the eastern Adriatic coast, offering new insights into the metallurgical background of archaeological types with distinct distribution patterns. The analysed axes date from the Middle to the early Late Bronze Age (17th − 14th centuries BC), a crucial period marked by intensified copper production in emerging Alpine mining districts and the decline of other metallurgical centres, such as those in eastern Serbia. Due to scarcity of analytical data and lack of closed contexts, the role of the eastern Adriatic within the dynamic copper supply networks of Bronze Age Europe has remained poorly understood so far. The region’s intermediary position between copper production centres in northeastern Italy and the inland Balkans, which from at least the beginning of the Late Bronze Age (14th century BC) were largely supplied with Italian copper is of particular relevance. The results presented here contribute to a more comprehensive understanding of regional metallurgical practices and help refine our reconstruction of the chronological and spatial dynamics of copper distribution across Central Europe, Italy, and the Balkans.

Non-invasive detection of internal foreign bodies in foods by using air-coupled ultrasound: case studies in beef burger patties and jelly plates - Gentil A. Collazos-Escobar; José M. Prats-Montalbán; Anabella S. Giacomozzi; José Benedito; Tomas E. Gómez Álvarez-Arenas; José V. García-Pérez (Journal of Food Engineering, 2026)

Similarities in metabolism and hypoxia tolerance of native and non-native florida freshwater fishes remain consistent in climate change scenarios - Benjamin A. Share; Aaron M. Hasenei; J. Matthew Hoch; Paul Arena; David W. Kerstetter (Biological Invasions, 2026)

A case for monitoring fungi of clinical relevance at beaches: enterococci measures do not correlate with all disease risks - Larissa Montás-Bravo; Helena M. Solo-Gabriele; Débora F. Gil; Ayaaz Amirali; Sebastian P. Arenas; Sofia Hoffman; Adriana Jimenez; Alexandre Mendonça; Rivka Reiner; Raquel Sabino; Konstantina Sarioglou; Mark E. Sharkey; et al. (Environmental Monitoring and Assessment, 2026)
Fungal disease is on the rise, coupled with fungal pathogens increasing in geographic range. Studies have shown that viable fungal pathogens may be present in beach sand and water, and consequently, efforts are ongoing in Europe to develop guidelines for fungi levels at beaches. In the USA, fungal diseases are a growing concern, and yet, they are not subject to public health reporting, and beach environments are currently not routinely monitored for fungal pathogens. This study measured fungal and enterococci levels at two beaches within a subtropical environment in Miami, FL. Samples were analyzed by culture-based methods, with fungi species confirmation by targeted PCR and sequencing. A unique aspect of this study is the analysis with higher incubation temperatures (37 °C and 40 °C) to isolate mesophilic fungi that can cause invasive infections. Results show that levels of fungi were strongly influenced by sample matrix (sand or water). The most common fungal species observed belonged to the Aspergillus and Candida genera, with the isolation of 25 taxa with reports of causing infections, of which 20 were previously reported to exhibit resistance to some or all classes of antifungals available. Results emphasize the need for fungal specific analyses to better understand beach-related disease risks. Given the current increase in cases of fungal diseases and the presence of viable fungi in the environment, integrating fungal measurements in routine microbiological monitoring programs is critical for assessing the beach transmission of pathogenic fungal disease and the control of emerging fungal pathogens.

Exploring Student Experiences in a Transdisciplinary Clinical Immersion Course on Needs Identification in Veteran and Service Member Healthcare Settings - Sarah Scheerer; Chloe Tenembaum; Aliza M. Lee; Devasmita Choudhury; Brad D. Hendershot; Andre Muelenaer; Ashley R. Taylor; Martha Sullivan; Pamela J. VandeVord; Elham Morshedzadeh; Christopher B. Arena (Biomedical Engineering Education, 2026)
Background As the number of BME clinical immersion experiences expands across university curricula, there is a growing opportunity for BME educators to share practical insights gained from implementing clinical immersion courses. Despite the growing scholarship exploring BME clinical immersions, a significant need for robust exploration remains as we work to understand the impact of such programs on student learning. Purpose To address this gap, the purpose of this work is to describe the design, implementation, and assessment of a BME course focused on clinical immersions in Service Member and Veteran healthcare environments. Methods We designed, implemented, and assessed student experiences in a new technical elective course in our undergraduate BME curriculum entitled Needs Identification in Healthcare . This paper analyzes data across the first three cohorts from students’ needs identification experiences, including working in transdisciplinary teams and immersion in Veteran and Service Member healthcare environments. The program structure is described with key elements that include (1) immersion partner collaboration, (2) team-based immersion experiences, (3) needs-finding emphasis, (4) team-based engineering design experiences, and (5) immersion assessment and evaluation. Techniques for student assessment include quantitative and qualitative survey items for investigating the program structure, complementary roles of engineers and designers, needs-finding ability, overall immersion experience, training content, faculty support, team effectiveness, self-reflection, and professional development. Results Overall, students had a high appreciation for the clinical immersion experience and benefited from their participation in the course in terms of their ability to problem solve, identify healthcare-related needs of Veterans, communicate with patients and providers, and work effectively in transdisciplinary teams wherein complementary roles of engineers and designers are valued. Conclusion Structured clinical immersion experiences that incorporate transdisciplinary teams and scoped healthcare environments promote student learning and professional development.

Tumour growth inhibitory effect of Ibervillea sonorae phytopreparations in cervical cancer xenografts - Max Vidal-Gutiérrez; Heriberto Torres-Moreno; Víctor M. Arenas-Luna; María Lilia Loredo-Mendoza; Farid Tejeda-Dominguez; Carlos Velazquez; Wagner Vilegas; Salomón Hernandez-Gutiérrez; Ramón E. Robles-Zepeda (Natural Product Research, 2025)

Is a warmer environment better for a high-mountain lizard? - Mirna C. Vera-Chávez; Donald B. Miles; Diego M. Arenas-Moreno; Fausto R. Méndez-de la Cruz (Journal of Thermal Biology, 2025)

P27-19 CLP criteria and ECHA guidance for classification of endocrine disruptors - K. Myöhänen; N. Andersson; M. Sobanska; F. Pellizzato; M. Arena (Toxicology Letters, 2025)

Evaluating the capability of tannic acid-modified biochar in sequestering metal ions and in enhancing soil health - L. Santorufo; G. Maglione; G. Costanzo; G. De Tommaso; F. De Paola; G. Roviello; E. Chianese; C. Ferone; F. Polimeno; M. Riccardi; G. Maisto; M. Iuliano; et al. (International Journal of Environmental Science and Technology, 2025)
Pollution of soils is one of the currently significant environmental concerns. Heavy metals that contaminate the soil can have harmful effects on crops, enter the food chain, and pose a threat to human health. Various approaches have been employed in the past to remediate heavy metal-contaminated soils for agricultural use, including the use of biochar and its modified forms through physical or chemical methods. In the present study, the suitability of tannic acid as a biochar modifier was evaluated for the first time with the aim of enhancing its ability to adsorb Cd and Pb, thereby reducing their transfer from soil to plants. A mesocosm trial was set-up using three treatments: control, unmodified biochar, and tannic acid-modified biochar and their impact was evaluated on soil characteristics and plant physiology. The FT-IR spectra demonstrate that tannic acid-modified biochar considerably improved its capability to absorb Cd but worsened those for Pb and this occurred due to an increase in oxygen-containing functional groups and a reduction in total pore volume, respectively. Tannic acid-modified biochar application increased the carbon and nitrogen concentrations in the soil, as well as the microbial biomass and activities. Lettuce plants grown on soil amended with modified biochar accumulated a low Cd amount in roots but a high Pb amount in leaves that reduced the photosynthetic pigments and the photosynthetic rates and increased the antioxidant response. It is found that tannic acid treatment of biochar is effective for the remediation of Cd-contaminated soils but not for those polluted by Pb.

High-resolution multi-technique analysis of a continuous sediment core of the Baza Formation at Barranco León (Guadix-Baza Basin, Granada): First petrophysical results - A. Santamaría Barragán; J. M. Parés; S. Colino García; A. Churruca Clemente; T. Fujioka; A. Serrano-Ramos; M. B. Toffolo; A. Alvaro Gallo; M. del Val; J. Iglesias-Cibanal; J. Jáimez; L. Miguens; et al. (Journal of Iberian Geology, 2025)

Dietary vitamin D intake and 2-year changes in cognitive function in older adults with overweight or obesity and metabolic syndrome - Héctor Vázquez-Lorente; Jiaqi Ni; Indira Paz-Graniel; Estefanía Toledo; Dolores Corella; Olga Castañer; J. Alfredo Martínez; Ángel M. Alonso-Gómez; Julia Wärnberg; Jesús Vioque; Dora Romaguera; José López-Miranda; et al. (GeroScience, 2025)
The protective role of dietary vitamin D intake on cognitive function is of interest, but evidence remains inconsistent. We aimed to evaluate the association between dietary vitamin D intake and 2-year cognitive changes in older adults at risk of cognitive decline. This longitudinal study comprised 5454 individuals (aged 55–75 years in men and 60–75 years in women) who exhibited overweight/obesity and metabolic syndrome. Data on dietary vitamin D intake was assessed using a validated 143-item food frequency questionnaire. Cognitive function was assessed through five composite scores derived from a comprehensive battery of eight neuropsychological tests, encompassing global cognitive function, general cognitive function, attention, executive function, and language domains. Multivariable-adjusted linear regression models were fitted to examine the association between energy-adjusted cumulative average dietary vitamin D intake over time and 2-year changes in cognitive function. After adjusting for multiple covariates, energy-adjusted cumulative average dietary vitamin D intake as a continuous variable was associated with greater 2-year improvements in global cognitive function ( β 1.18 × 10 −2 ; 95% CI 0.19 × 10 −2 to 2.17 × 10 −2 ), executive function ( β 1.12 × 10 −2 ; 95% CI 0.03 × 10 −2 to 2.21 × 10 −2 ), and language ( β 1.61 × 10 −2 ; 95% CI 0.43 × 10 −2 to 2.78 × 10 −2 ). Additionally, the higher cumulative average dietary vitamin D intake quartile was associated with an increase in global cognitive function ( β 7.10 × 10 −2 ; 95% CI 0.59 × 10 −2 to 13.6 × 10 −2 ), language ( β 7.07 × 10 −2 ; 95% CI − 0.52 × 10 −2 to 14.7 × 10 −2 ), and a lower decline in attention ( β 9.58 × 10 −2 ; 95% CI 1.60 × 10 −2 to 17.5 × 10 −2 ). A higher dietary vitamin D intake was associated with modest favorable changes in cognitive function and a reduced cognitive decline over a 2-year period. These findings highlight the need for further research to explore the potential benefits of boosting dietary vitamin D intake for cognitive health in older adults.

Petrogenesis of ultramafic rocks from the Neoproterozoic Bou Azzer Ophiolite (Morocco): new insights into a long-standing geodynamic question - N. Pujol-Solà; J.A. Proenza; A. Cambeses; F. Haissen; H. Escalona-Orellana; D. Domínguez-Carretero; I. Novo-Fernández; R. Arenas; L. Maacha; M. Ikenne; A. Garcia-Casco (International Geology Review, 2025)

Diverse ecological responses of foraminifera to the Middle Eocene Climatic Optimum (MECO) in shallow-water settings (Provençal Domain, NW Italy) - A. Gandolfi; V.M. Giraldo-Gómez; L. Arena; V. Luciani; C.A. Papazzoni; J. Pignatti; M. Piazza; L. Kocsis; C. Baumgartner; A. Briguglio (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Arc sections correlation along the Gondwana margin: Dynamic shifts tracked by detrital zircon - Esther Rojo-Pérez; Javier Fernández-Suárez; José M. Fuenlabrada; Richard Albert; Rubén Díez Fernández; Sonia Sánchez Martínez; Irene Novo-Fernández; Diana Moreno-Martín; Axel Gerdes; Ricardo Arenas (Gondwana Research, 2025)

Foraminifera and sediments cored from the bottom of the Faanu Mudugau Blue Hole, Ari Atoll, Maldives: Diversity, taphonomy and environmental reconstruction of an inhabitable substrate - Victor M. Giraldo-Gómez; Luca Arena; Marco Capello; Laura Cutroneo; Annalisa Azzola; Monica Montefalcone; Antonino Briguglio (Marine Geology, 2024)

Alkaline Devonian magmatism of the Menorca Island: Tracking the mantle isotopic sources in the realm of the western Paleo-Tethys Ocean - Chris Timoner; Ricardo Arenas; José M. Fuenlabrada; Juan A. Moreno; Esther Rojo-Pérez (Chemical Geology, 2024)

Effects of chronic insecticide exposure on neuronal network development in vitro in rat cortical cultures - Lennart V. J. van Melis; Anneloes M. Peerdeman; Celia Arenas González; Regina G. D. M. van Kleef; J. Pepijn Wopken; Remco H. S. Westerink (Archives of Toxicology, 2024)
Developmental exposure to carbamates, organophosphates, and pyrethroids has been associated with impaired neurodevelopmental outcomes. Sex-specific differences following chronic insecticide exposure are rather common in vivo. Therefore, we assessed the chronic effects of in vitro exposure to different carbamates (carbaryl, methomyl and aldicarb), organophosphates [chlorpyrifos (CPF), chlorpyrifos-oxon (CPO), and 3,5,6,trichloropyridinol (TCP)], and pyrethroids [permethrin, alpha-cypermethrin and 3-phenoxy benzoic acid (3-PBA)] on neuronal network development in sex-separated rat primary cortical cultures using micro-electrode array (MEA) recordings. Our results indicate that exposure for 1 week to carbaryl inhibited neurodevelopment in male cultures, while a hyperexcitation was observed in female cultures. Methomyl and aldicarb evoked a hyperexcitation after 2 weeks of exposure, which was more pronounced in female cultures. In contrast to acute MEA results, exposure to ≥ 10 µM CPF caused hyperexcitation in both sexes after 10 days. Interestingly, exposure to 10 µM CPO induced a clear hyperexcitation after 10 days of exposure in male but not female cultures. Exposure to 100 µM CPO strongly inhibited neuronal development. Exposure to the type I pyrethroid permethrin resulted in a hyperexcitation at 10 µM and a decrease in neuronal development at 100 µM. In comparison, exposure to ≥ 10 µM of the type II pyrethroid alpha-cypermethrin decreased neuronal development. In female but not in male cultures, exposure to 1 and 10 µM permethrin changed (network) burst patterns, with female cultures having shorter (network) bursts with fewer spikes per (network) burst. Together, these results show that MEA recordings are suitable for measuring sex-specific developmental neurotoxicity in vitro. Additionally, pyrethroid exposure induced effects on neuronal network development at human-relevant concentrations. Finally, chronic exposure has different effects on neuronal functioning compared to acute exposure, highlighting the value of both exposure paradigms.

European Network for Optimization of Veterinary Antimicrobial Therapy (ENOVAT) guidelines for antimicrobial use in canine acute diarrhoea - L.R. Jessen; M. Werner; D. Singleton; C. Prior; F. Foroutan; A.A. Ferran; C. Arenas; C. R. Bjørnvad; E. Lavy; F. Allerton; K. Allensbach; L. Guardabassi; et al. (The Veterinary Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

P20-10 Embracing regulatory compliance: Genetox meets generation SEND - S. Salazar Arenas; C. Bapat; M. Ellison; M. Wasko; F. Hall (Toxicology Letters, 2024)

Role of peripheral inflammation in minimal hepatic encephalopathy - Marta Llansola; Paula Izquierdo-Altarejos; Carmina Montoliu; Gergana Mincheva; Andrea Palomares-Rodriguez; María A. Pedrosa; Yaiza M. Arenas; Vicente Felipo (Metabolic Brain Disease, 2024)

Wind dispersal differences between rotifer cryptic species: a proof of principle from a wind tunnel experiment - Cristina Arenas-Sánchez; Luc Brendonck; Eduardo M. García-Roger; María José Carmona; Raquel Ortells (Hydrobiologia, 2024)
Wind is expected to be one of the main vectors of passive dispersal for small zooplankters between discrete, unconnected habitats. However, little is known about the differences in the dispersal capacity of species in relation to their propagule traits. Here we assessed the effect of volume and weight of diapausing eggs and substrate granulometry on the dispersal departure propensity of two differently body-sized rotifer species belonging to the Brachionus plicatilis complex using a wind tunnel experiment. Diapausing eggs of the larger species were also larger but, counterintuitively, were lifted by the wind to a greater extent than those of the smaller one. Further, diapausing eggs on the finer substrate were more exposed to the wind than those over the coarser one, and therefore higher departure rates were observed in the former. Overall, results show that wind is a relevant dispersal vector for the rotifers of the B. plicatilis species complex, with egg morphological traits and substrate granulometry being important factors modulating their dispersal. This study is a proof of concept for the departure phase of dispersal. Further studies on transfer and settlement phases are needed to get a complete picture of the dispersal potential of these organisms.

Perezone and its phenyl glycine derivative induce cytotoxicity via caspases on human glial cancer cells - M. Mirian Estévez-Carmona; M. Teresa Ramírez-Apan; Montserrat Zaragoza-Ojeda; Anita Vega-Miranda; Francisco Arenas-Huertero; William F. Reynolds; Marco A. Obregón-Mendoza (Natural Product Research, 2024)

A novel membrane-based process to concentrate nutrients from sidestreams of an Urban Wastewater Treatment Plant through captured carbon dioxide from biogas - Judith González-Arias; Francisco M. Baena-Moreno; Mónica Rodríguez-Galán; Benito Navarrete; Luis F. Vilches-Arenas (Science of The Total Environment, 2024)

Effect of a nutritional intervention based on an energy-reduced Mediterranean diet on environmental impact - Laura Álvarez-Álvarez; María Rubín-García; Facundo Vitelli-Storelli; Silvia García; Cristina Bouzas; Miguel Ángel Martínez-González; Dolores Corella; Jordi Salas-Salvadó; Mireia Malcampo; J. Alfredo Martínez; Ángel M. Alonso-Gómez; Julia Wärnberg; et al. (Science of The Total Environment, 2024)

Origin and evolution of Cadomian magmatism in SW Iberia: from subduction onset and arc building to a tectonic switching - Esther Rojo-Pérez; José M Fuenlabrada; Rubén Díez Fernández; Ricardo Arenas (International Geology Review, 2024)

Multimodal brain age prediction using machine learning: combining structural MRI and 5-HT2AR PET-derived features - Ruben P. Dörfel; Joan M. Arenas-Gomez; Claus Svarer; Melanie Ganz; Gitte M. Knudsen; Jonas E. Svensson; Pontus Plavén-Sigray (GeroScience, 2024)
To better assess the pathology of neurodegenerative disorders and the efficacy of neuroprotective interventions, it is necessary to develop biomarkers that can accurately capture age-related biological changes in the human brain. Brain serotonin 2A receptors (5-HT2AR) show a particularly profound age-related decline and are also reduced in neurodegenerative disorders, such as Alzheimer’s disease. This study investigates whether the decline in 5-HT2AR binding, measured in vivo using positron emission tomography (PET), can be used as a biomarker for brain aging. Specifically, we aim to (1) predict brain age using 5-HT2AR binding outcomes, (2) compare 5-HT2AR-based predictions of brain age to predictions based on gray matter (GM) volume, as determined with structural magnetic resonance imaging (MRI), and (3) investigate whether combining 5-HT2AR and GM volume data improves prediction. We used PET and MR images from 209 healthy individuals aged between 18 and 85 years (mean = 38, std = 18) and estimated 5-HT2AR binding and GM volume for 14 cortical and subcortical regions. Different machine learning algorithms were applied to predict chronological age based on 5-HT2AR binding, GM volume, and the combined measures. The mean absolute error (MAE) and a cross-validation approach were used for evaluation and model comparison. We find that both the cerebral 5-HT2AR binding (mean MAE = 6.63 years, std = 0.74 years) and GM volume (mean MAE = 6.95 years, std = 0.83 years) predict chronological age accurately. Combining the two measures improves the prediction further (mean MAE = 5.54 years, std = 0.68). In conclusion, 5-HT2AR binding measured using PET might be useful for improving the quantification of a biomarker for brain aging.

A Paleogene mixed carbonate-siliciclastic system in the western Tethys: spectral gamma-ray as a tool for the reconstruction of paleoclimate and transgressive-regressive cycles - Victor M. Giraldo-Gómez; Michele Piazza; Luca Arena; Andrea Baucon; Antonella Gandolfi; Cesare A. Papazzoni; Johannes Pignatti; Antonino Briguglio (Marine and Petroleum Geology, 2024)

Continuous nitrite and nitrate monitoring of recirculating aquaculture systems using a deployable ion chromatography-based analyser - Meritxell Grau Butinyac; Valeria Arenas Montaño; Jamie Downes; Neil M. Ruane; Elizabeth Ryder; Fintan Egan; Thomas Staessen; Brett Paull; Eoin Murray (Aquaculture International, 2024)

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

Artificial Light at Night Reduces Flashing in Photinus and Photuris Fireflies During Courtship and Predation - Juan S. Hillón-Salas; Juan D. Pineda-Dueñas; Ana M. Romero-Chacón; Juliana Fonseca-Tellez; Manuela Cardona-Restrepo; Sofía C. Garrido-Villegas; Diego Mejía-Tovar; Camilo Arenas-Ríos; Laia Gaitán-Botero; Zulma S. Barón-Garzón; Andrés F. Robayo-Salek; Harold Pulido-Guarín; et al. (Journal of Insect Behavior, 2024)
Artificial light at night (ALAN) affects species-specific communication in a wide range of nocturnal species, including fireflies (Lampyridae). Fireflies rely on bioluminescent signals for communicating. In this study, we conducted two manipulative field experiments to evaluate the effect of artificial light at night on the flashing activity of male and female neotropical fireflies during courtship and predation. Our results showed a significant reduction in the flashing activity of both males and females exposed to ALAN during courtship and predation. Remarkably, the effect of ALAN on male flashing activity seems to be independent of female flashing activity. In conclusion, ALAN disrupts bioluminescent intraspecific (courtship) and interspecific (predation) communication, which in turn could influence mating success, thus negatively affecting neotropical firefly populations in the long term. Our findings contribute to understanding the challenges faced by neotropical firefly communities in the presence of ALAN.

Plant metabolic response to stress in an arid ecosystem is mediated by the presence of neighbors - Alicia Montesinos‐Navarro; Maria F. López‐Climent; Rosa M. Pérez‐Clemente; Cristina Arenas‐Sánchez; Ricardo Sánchez‐Martín; Aurelio Gómez‐Cadenas; Miguel Verdú (Ecology, 2024)
Plant neighbors in arid environments can ameliorate abiotic stress by reducing insolation, but they also attract herbivores and pathogens, especially when neighbors are close relatives that share similar antagonists. Plants' metabolic profiles provide a chemical fingerprint of the physiological processes behind plant responses to different environmental stresses. For example, abscisic acid and proline, mainly involved in stomatal closure and osmotic adjustment, can induce plant responses to abiotic stress, while jasmonic acid and salicylic acid primarily regulate plant defense to herbivory or pathogens. Neighbor plants can generate contrasting ecological contexts, modulating plant responses to abiotic and biotic stresses. We hypothesize that plant metabolic profile is modulated by its neighbors in a vegetation patch, expecting a higher investment in metabolites related to biotic‐stress tolerance (i.e., herbivory or pathogens) when growing associated with other plants, especially to phylogenetically close relatives, compared to plants growing alone. We show that plants from five species growing with neighbors invest more in biotic‐stress tolerance while their conspecifics, growing alone, invest more in abiotic‐stress tolerance. This tendency in plants' metabolic profiles was not affected by the phylogenetic diversity of their neighborhood. Linking physiological snapshots with community processes can contribute to elucidating metabolic profiles derived from plant–plant interactions.

Evaluation of susceptibility of commercial citrus rootstocks to white root rot incited by Rosellinia necatrix - Juan M. Arjona-López; José A. Monferrer-Salinas; José Luís Cantero-Sánchez; Estefanía Romero-Rodríguez; Carlos J. López-Herrera; Francisco J. Arenas-Arenas (Journal of Plant Pathology, 2024)

Efficacy of antimicrobial and nutraceutical treatment for canine acute diarrhoea: A systematic review and meta-analysis for European Network for Optimization of Antimicrobial Therapy (ENOVAT) guidelines - K. Scahill; L.R. Jessen; C. Prior; D. Singleton; F. Foroutan; A.A. Ferran; C. Arenas; C.R. Bjørnvad; E. Lavy; F. Allerton; J.S. Weese; K. Allenspach; et al. (The Veterinary Journal, 2024)

Exposure to ambient air toxicants and the risk of amyotrophic lateral sclerosis (ALS): A matched case control study - Fan Wu; Angela M. Malek; Jeanine M. Buchanich; Vincent C. Arena; Judith R. Rager; Ravi K. Sharma; John E. Vena; Todd Bear; Evelyn O. Talbott (Environmental Research, 2024)

Geochemistry and mineralogy of muds and thermal waters from mud volcanoes in the NW Caribbean Coast of Colombia and their potential for pelotherapy - Maurizio Palmisano; Giuseppina Balassone; Sabino Maggi; Alexander Armesto Arenas; Iber M. Banda Guerra; Luis E. Correa Valero; Feliciano Ippolito; Nicola Mondillo; David F. Morales Giraldo; Angela Mormone; Annamaria Pellino; Francesco Putzolu; et al. (CATENA, 2024)

Short-term middle Eocene (Bartonian) paleoenvironmental changes in the sedimentary succession of Olivetta San Michele (NW Italy): the response of shallow-water biota to climate in NW Tethys - Luca Arena; Victor M. Giraldo-Gómez; Andrea Baucon; Michele Piazza; Cesare A. Papazzoni; Johannes Pignatti; Antonella Gandolfi; Antonino Briguglio (Facies, 2024)
This study focuses on the paleontological content of the middle Eocene (Bartonian) carbonate–siliciclastic sediments of the Capo Mortola Calcarenite Formation from Olivetta San Michele (Liguria, Italy). Along the succession, there are significant paleoecological changes triggered by the variation in neritic input as a consequence of tectonic and climatic instability. Among microfossils, nummulitids prevail, followed by orthophragmines, smaller benthic, and planktonic foraminifera, whereas mollusks and ichnofossils are the most abundant macrofossils. The sudden changes in the benthic communities due to the progressive increase in fluvial input are recorded throughout the sedimentary succession. An increase in water turbidity caused stressful conditions for autotrophic taxa, reducing their size and abundance. In contrast, filter feeders became dominant, suggesting an increase in dissolved and suspended nutrients. Ichnological analysis shows environmental fluctuations controlled by the transport of neritic material offshore, thus confirming the general deepening trend of the studied succession. In the upper part of the succession, we recorded an alternation between gravity flows and marly sediments that are interpreted as short-term alternations between low and intense precipitations. The gravity flows yield taxa such as larger benthic foraminifera (LBF), smaller benthic and planktonic foraminifera, mollusks, and corals. In turn, marls display only a few LBF and abundant smaller benthic and planktonic foraminifera. In these intervals, the increase in planktonic foraminifera also suggests a deepening of the carbonate ramp coinciding with a reduction of light that did not favor the development of LBF. These changes are probably related to the climatic dynamics that occurred in the Bartonian in the western Tethys.

Opening and closure of Cadomian peri-Gondwanan oceans: age and evolution of the Mérida Ophiolite (SW Iberia) - R. Arenas; E. Rojo-Pérez; R. Díez Fernández; R. Albert; I. Novo-Fernández; S. Sánchez Martínez; J. M. Fuenlabrada; P. Andonaegui; D. Moreno-Martín; A. Gerdes; A. Garcia-Casco (International Geology Review, 2024)

Understanding different dominance patterns in western Amazonian forests - Laura Matas‐Granados; Frederick C. Draper; Luis Cayuela; Julia G. de Aledo; Gabriel Arellano; Celina Ben Saadi; Timothy R. Baker; Oliver L. Phillips; Eurídice N. Honorio Coronado; Kalle Ruokolainen; Roosevelt García‐Villacorta; Katherine H. Roucoux; et al. (Ecology Letters, 2024)
Dominance of neotropical tree communities by a few species is widely documented, but dominant trees show a variety of distributional patterns still poorly understood. Here, we used 503 forest inventory plots (93,719 individuals ≥2.5 cm diameter, 2609 species) to explore the relationships between local abundance, regional frequency and spatial aggregation of dominant species in four main habitat types in western Amazonia. Although the abundance‐occupancy relationship is positive for the full dataset, we found that among dominant Amazonian tree species, there is a strong negative relationship between local abundance and regional frequency and/or spatial aggregation across habitat types. Our findings suggest an ecological trade‐off whereby dominant species can be locally abundant ( local dominants ) or regionally widespread ( widespread dominants ), but rarely both ( oligarchs ). Given the importance of dominant species as drivers of diversity and ecosystem functioning, unravelling different dominance patterns is a research priority to direct conservation efforts in Amazonian forests.

Influence of oxygen vacancies, surface composition, and crystallite size on the photoelectrochemical oxidation activity of C,N-codoped TiO2 for cefadroxil abatement along with O3 - Daniela Palomares-Reyna; Roberto L. Palomino-Resendiz; Ulises M. García-Pérez; Iliana Fuentes-Camargo; Luis Lartundo-Rojas; Fabiola S. Sosa-Rodríguez; Vítor J.P. Vilar; Jorge Vazquez-Arenas (Chemosphere, 2023)

Analysis of SARS-CoV-2 in wastewater for prevalence estimation and investigating clinical diagnostic test biases - Mattia Mattei; Rosa M. Pintó; Susana Guix; Albert Bosch; Alex Arenas (Water Research, 2023)

Microplastics in surface water of the Bay of Asunción, Paraguay - Diana Beatriz Diez-Pérez; Inés Arenas; Erenia Maidana; Adrián López-Rosales; Jose M. Andrade; Soledad Muniategui-Lorenzo (Marine Pollution Bulletin, 2023)

Superior performance of a trailing edge low-latitude population of an intertidal marine invertebrate - Jeffrey Levinton; Brooke Arena; Riley Pena; M. Zachary Darnell (Journal of Experimental Marine Biology and Ecology, 2023)

Sustained Hyperammonemia Activates NF-κB in Purkinje Neurons Through Activation of the TrkB-PI3K-AKT Pathway by Microglia-Derived BDNF in a Rat Model of Minimal Hepatic Encephalopathy - Yaiza M. Arenas; Vicente Felipo (Molecular Neurobiology, 2023)

Sphalerite oxidation simulating acidic, circumneutral and alkaline conditions to account for weathering behavior and Zn release - Fabiola S. Sosa-Rodríguez; Jorge Vazquez-Arenas; Patricia Ponce-Peña; Antonio Aragón-Piña; Martine Mallet; Gabriel Trejo-Córdova; Diola M. Núñez-Ramirez; Miguel A. Escobedo-Bretado; René H. Lara (Journal of Geochemical Exploration, 2023)

Range‐edge populations of seaweeds show niche unfilling and poor adaptation to increased temperatures - Sandra Hernández; Ana G. García; Francisco Arenas; M. Pilar Escribano; Alexander Jueterbock; Olivier De Clerck; Christine A. Maggs; João N. Franco; Brezo D. C. Martínez (Journal of Biogeography, 2023)
Aim Global warming is affecting the distribution of species worldwide, but the level of adaptation of edge populations to warmer temperatures remains an open question. Here, we assess the thermal tolerance of populations of two habitat‐forming seaweeds along their latitudinal range, using thermal niche unfilling to assess their resilience to global warming. Location European Atlantic coastline. Taxon Ascophyllum nodosum (Linnaeus) Le Jolis (Phaeophyceae) and Chondrus crispus Stackhouse (Rhodophyta). Methods We studied the ecotypic variation in upper survival temperatures (USTs) by measuring survival and growth of adults representing populations under a gradient of seawater temperature (12–30°C). Comparing the USTs with maximum seawater temperatures obtained from satellites, we investigated safety margins and niche unfilling states, both in recent history and under future climate scenarios. Results USTs (≈24°C) did not differ significantly between populations, except for higher values (27.9°C) for the northernmost populations (cold edge) of A . nodosum . Populations of both species had thermal safety margins over the last few decades (from 1982 to 2021). However, projections based on USTs showed that in several years these margins have been eliminated and will completely disappear in the Bay of Biscay under RCP4.5 and RCP6.0 2090–2100 IPCC scenarios for C . crispus and under RCP8.5 for both species, threatening the populations there. Main Conclusions Southern marginal populations were not better adapted to global warming than populations elsewhere. Both seaweed species tolerated higher temperatures than the ambient maxima, suggesting a thermal niche unfilling state with thermal safety margins in their recent history. However, those are being depleted by ongoing climate change and this trend is predicted to increase. Marine heat waves are important threats to these habitat‐forming species, transiently reducing or even eliminating safety margins in the hottest parts of the European Atlantic coastline, contributing to explaining the distributional gap there.

The impact of local and climate change drivers on the formation, dynamics, and potential recurrence of a massive fish-killing microalgal bloom in Patagonian fjord - Patricio A. Díaz; Iván Pérez-Santos; Leila Basti; René Garreaud; Elias Pinilla; Facundo Barrera; Alfredo Tello; Camila Schwerter; Sara Arenas-Uribe; Camila Soto-Riquelme; Pilar Navarro; Manuel Díaz; et al. (Science of The Total Environment, 2023)

Long-term air pollution and risk of amyotrophic lateral sclerosis mortality in the Women's Health Initiative cohort - Angela M. Malek; Vincent C. Arena; Ruopu Song; Eric A. Whitsel; Judith R. Rager; James Stewart; Jeff D. Yanosky; Duanping Liao; Evelyn O. Talbott (Environmental Research, 2023)

Sleep duration and lipid metabolism in patients with diabetes mellitus: from the POWER2DM study - Isabel Perez-Corral; Francisco Gomez-Delgado; Merel M. Ruissen; Jose D. Torres-Peña; Antonio P. Arenas-de Larriva; Jacob K. Sont; Albert A. de Graaf; Bas S. Uitbeijerse; Eelco J. P. de Koning; Javier Delgado-Lista (Sleep and Biological Rhythms, 2022)

Setting Performance Indicators for Coastal Marine Protected Areas: An Expert-Based Methodology - Mariana Cardoso-Andrade; Henrique Queiroga; Mafalda Rangel; Inês Sousa; Adela Belackova; Luís Bentes; Frederico Oliveira; Pedro Monteiro; Nuno Sales Henriques; Carlos M. L. Afonso; Ana F. Silva; Bernardo R. Quintella; et al. (Frontiers in Marine Science, 2022)
Marine Protected Areas (MPAs) require effective indicators to assess their performance, in compliance with the goals of relevant national and international commitments. Achieving and prioritizing shortlists of multidisciplinary indicators demands a significant effort from specialists to depict the multiple conservation and socioeconomic interests, and the large complexity of natural systems. The present paper describes a structured expert-based methodology (process and outputs) to co-define a list of multidisciplinary MPA performance indicators. This work was promoted by the management authority of coastal MPAs in mainland Portugal to gather a consensual and feasible list of indicators that would guide the design of a future national monitoring program. Hence, Portuguese coastal MPAs served as a case study to develop such a process between 2019 and 2020. In the end, participants (1) agreed on a shortlist of prioritized indicators ( i.e. , environmental, governance, and socioeconomic indicators) and (2) defined minimum monitoring frequencies for the indicators in this list, compatible with the potential replicability of the associated survey methods. The present approach recommends that management plans incorporate monitoring procedures and survey methods, with a validated list of indicators and associated monitoring periodicity, agreed among researchers, MPA managers and governance experts. The proposed methodology, and the lessons learned from it, can support future processes aiming to define and prioritize MPA performance indicators.

Berberis burruyacuensis O. R. Dantur, S. Radice, E. Giordani, A. Papini sp. nov. (Berberidaceae): a new species - M. Gori; S. Biricolti; S. Pedrazzani; E. Giordani; A. Papini; O. R. Dantur; M. E. Arena; S. Radice (Genetic Resources and Crop Evolution, 2021)

Geochemistry and Sm–Nd isotopic sources of Late Ediacaran siliciclastic series in the Ossa–Morena Complex: Iberian–Bohemian correlations - Esther Rojo-Pérez; José M. Fuenlabrada; Ulf Linnemann; Ricardo Arenas; Sonia Sánchez Martínez; Rubén Díez Fernández; Luis Miguel Martín Parra; Jerónimo Matas; Pilar Andonaegui; Javier Fernández-Suárez (International Journal of Earth Sciences, 2021)

Morphological and genetic variability associated with environmental variation in two species of Pseudodiploria Fukami, Budd & Knowlton, 2012 (Cnidaria: Anthozoa: Scleractinia) - N. A. Colín-García; J. E. Campos; J. L. Tello-Musi; X. Chiappa-Carrara; M. L. Arena-Ortiz; Z. H. Forsman; S. Milena; J. Escobar; J. E. Arias-González (Marine Biodiversity, 2020)

Trends in the food and sports nutrition industry: A review - Marta Arenas-Jal; J. M. Suñé-Negre; Pilar Pérez-Lozano; Encarna García-Montoya (Critical Reviews in Food Science and Nutrition, 2020)

The antioxidant power of horseradish, Armoracia rusticana , underlies antimicrobial and antiradical effects, exerted in vitro - Simona Manuguerra; Letteria Caccamo; Monique Mancuso; Rosaria Arena; Alessandro C. Rappazzo; Lucrezia Genovese; Andrea Santulli; Concetta M. Messina; G. Maricchiolo (Natural Product Research, 2020)

Improving ozonation to remove carbamazepine through ozone-assisted catalysis using different NiO concentrations - Claudia M. Aguilar; Jorge Vazquez-Arenas; Omar O. Castillo-Araiza; Julia L. Rodríguez; Isaac Chairez; Eric Salinas; Tatiana Poznyak (Environmental Science and Pollution Research, 2020)

A morphological, reproductive, and molt phenology database for 379 bird species from the Colombian Tropical Andes - Leydy J. Cardona‐Salazar; Yeny A. Benavides‐Ossa; Ángela M. Vargas‐Daza; Juan F. Betancurt‐Grisales; Mauricio Bohada‐Murillo; Estefani T. Martínez‐Sánchez; Marelid Cardona‐Romero; Ana Busi; William D. Tobón‐Escobar; Mateo Ortíz‐Giraldo; Daniela Gómez Castillo; Johnathan Alvarez‐Londoño; et al. (Ecology, 2020)
The Colombian Tropical Andes are one of the regions with highest bird diversity on Earth. However, information on bird morphology, reproductive phenology, and molt is particularly scarce in this region. Also, this region is heavily impacted by deforestation, and it is vulnerable to climate change. Hence, providing baseline information on life history and morphological traits will be essential to support future research on functional diversity, climate change effects, conservation, evolution, and phenology. To fill this gap, we have compiled information on bird distribution, morphology, molt, and reproductive phenology at 52 localities of the Department of Caldas, covering an elevation range between 148 and 3845 m. This compilation comprises a wide range of habitats, including native forests, forestry plantations, croplands, and paramo. Our database presents information for 3,398 records belonging to 379 bird species (representing 23 orders, 53 families, and 258 genera). From those records, 2,843 correspond to information collected in the field between 2008 and 2019, and the remaining 555 records correspond to specimens deposited in the Natural History Museum of the Caldas University, collected between 1969 and 2014. We measured nine morphological traits from all specimens: total culmen, gape, bill width, bill depth, tarsus, wing length, tail length, total length, and mass. We also have reproductive condition information for 257 species and molt information available for 378 species. The information contained in this data set represents ~20% of the Colombian avifauna and ~11% of the bird species richness in South America. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Antidiabetic, cytotoxic and antioxidant activities of oil extracted from Acrocomia aculeata pulp - Perla V. B. da Silva; Marianne M. Ramiro; Edna K. K. Iriguchi; William A. Corrêa; Jennifer Lowe; Claudia A. L. Cardoso; Arielle C. Arena; Cândida A. L. Kassuya; Rozanna M. Muzzi (Natural Product Research, 2019)

Extracellular cGMP Reverses Altered Membrane Expression of AMPA Receptors in Hippocampus of Hyperammonemic Rats: Underlying Mechanisms - Lucas Taoro-Gonzalez; Yaiza M. Arenas; Andrea Cabrera-Pastor; Vicente Felipo (Molecular Neurobiology, 2019)

Heavy metals in the volcanic and peri-urban terrain watershed of the River Yautepec, Mexico - Silvia Viridiana Vargas-Solano; Francisco Rodríguez-González; Martha Lucia Arenas-Ocampo; Rita Martínez-Velarde; S. B. Sujitha; M. P. Jonathan (Environmental Monitoring and Assessment, 2019)

Gene expression analysis in peripheral blood cells of patients with hereditary leiomyomatosis and renal cell cancer syndrome (HLRCC): identification of NRF2 pathway activation - Carolina Arenas Valencia; Liliana Lopez Kleine; Andres M. Pinzon Velasco; Andrea Y. Cardona Barreto; Clara E. Arteaga Diaz (Familial Cancer, 2018)

Baseline prepulse inhibition of the startle reflex predicts the sensitivity to the conditioned rewarding effects of cocaine in male and female mice - M. C. Arenas; C. I. Navarro-Francés; S. Montagud-Romero; J. Miñarro; C. Manzanedo (Psychopharmacology, 2018)

Successional convergence in experimentally disturbed intertidal communities - Gustavo M. Martins; Francisco Arenas; Fernando Tuya; Rubén Ramírez; Ana I. Neto; Stuart R. Jenkins (Oecologia, 2018)

Contrasting evolutionary patterns in populations of demersal sharks throughout the western Mediterranean - Sergio Ramírez-Amaro; Antonia Picornell; Miguel Arenas; Jose A. Castro; Enric Massutí; M. M. Ramon; Bàrbara Terrasa (Marine Biology, 2018)

Exploring Institutional Mechanisms for Scientific Input into the Management Cycle of the National Protected Area Network of Peru: Gaps and Opportunities - M. D. López-Rodríguez; H. Castro; M. Arenas; J. M. Requena-Mullor; A. Cano; E. Valenzuela; J. Cabello (Environmental Management, 2017)

Public policy performance for social development: solar energy approach to assess technological outcome in Mexico City Metropolitan Area - Angel Raúl Arenas-Aquino; Y. Matsumoto-Kuwabara; M. Kleiche-Dray (Environmental Science and Pollution Research, 2017)

Genetic and morphological analysis of Berberis microphylla G. Forst. accessions in southern Tierra del Fuego - E. Giordani; M. Müller; F. Gambineri; D. Paffetti; M. Arena; S. Radice (Plant Biosystems, 2017)

Self‐fertilization, long‐distance flash invasion and biogeography shape the population structure of Pseudosuccinea columella at the worldwide scale - M. Lounnas; A. C. Correa; A. A. Vázquez; A. Dia; J. S. Escobar; A. Nicot; J. Arenas; R. Ayaqui; M. P. Dubois; T. Gimenez; A. Gutiérrez; C. González‐Ramírez; et al. (Molecular Ecology, 2017)
Population genetic studies are efficient for inferring the invasion history based on a comparison of native and invasive populations, especially when conducted at species scale. An expected outcome in invasive populations is variability loss, and this is especially true in self‐fertilizing species. We here focus on the self‐fertilizing Pseudosuccinea columella , an invasive hermaphroditic freshwater snail that has greatly expanded its geographic distribution and that acts as intermediate host of Fasciola hepatica , the causative agent of human and veterinary fasciolosis. We evaluated the distribution of genetic diversity at the largest geographic scale analysed to date in this species by surveying 80 populations collected during 16 years from 14 countries, using eight nuclear microsatellites and two mitochondrial genes. As expected, populations from North America, the putative origin area, were strongly structured by selfing and history and harboured much more genetic variability than invasive populations. We found high selfing rates (when it was possible to infer it), none‐to‐low genetic variability and strong population structure in most invasive populations. Strikingly, we found a unique genotype/haplotype in populations from eight invaded regions sampled all over the world. Moreover, snail populations resistant to infection by the parasite are genetically distinct from susceptible populations. Our results are compatible with repeated introductions in South America and flash worldwide invasion by this unique genotype/haplotype. Our study illustrates the population genetic consequences of biological invasion in a highly selfing species at very large geographic scale. We discuss how such a large‐scale flash invasion may affect the spread of fasciolosis.

Topiramate increases the rewarding properties of cocaine in young-adult mice limiting its clinical usefulness - M. C. Arenas; A. Mateos-García; C. Manzanedo; M. Rodríguez-Arias; M. A. Aguilar; F. Navarrete; M. S. García Gutiérrez; J. Manzanares; J. Miñarro (Psychopharmacology, 2016)

Eco-physiological response to water stress of drought-tolerant and drought-sensitive tomato genotypes - M. M. Rigano; C. Arena; A. Di Matteo; S. Sellitto; L. Frusciante; A. Barone (Plant Biosystems, 2016)

Ecological connectivity shapes quasispecies structure of RNA viruses in an Antarctic lake - A. López‐Bueno; A. Rastrojo; R. Peiró; M. Arenas; A. Alcamí (Molecular Ecology, 2015)
RNA viruses exist as complex mixtures of genotypes, known as quasispecies, where the evolution potential resides in the whole community of related genotypes. Quasispecies structure and dynamics have been studied in detail for virus infecting animals and plants but remain unexplored for those infecting micro‐organisms in environmental samples. We report the first metagenomic study of RNA viruses in an Antarctic lake (Lake Limnopolar, Livingston Island). Similar to low‐latitude aquatic environments, this lake harbours an RNA virome dominated by positive single‐strand RNA viruses from the order Picornavirales probably infecting micro‐organisms. Antarctic picorna‐like virus 1 ( APLV 1), one of the most abundant viruses in the lake, does not incorporate any mutation in the consensus sequence from 2006 to 2010 and shows stable quasispecies with low‐complexity indexes. By contrast, APLV 2‐ APLV 3 are detected in the lake water exclusively in summer samples and are major constituents of surrounding cyanobacterial mats. Their quasispecies exhibit low complexity in cyanobacterial mat, but their run‐off‐mediated transfer to the lake results in a remarkable increase of complexity that may reflect the convergence of different viral quasispecies from the catchment area or replication in a more diverse host community. This is the first example of viral quasispecies from natural aquatic ecosystems and points to ecological connectivity as a modulating factor of quasispecies complexity.

Sex differences in the long-lasting consequences of adolescent ethanol exposure for the rewarding effects of cocaine in mice - A Mateos-García; C Manzanedo; M Rodríguez-Arias; M. A. Aguilar; E. Reig-Sanchis; C. I. Navarro-Francés; O. Valverde; J. Miñarro; M. C. Arenas (Psychopharmacology, 2015)

Role of CB2 receptors in social and aggressive behavior in male mice - Marta Rodríguez-Arias; Francisco Navarrete; M. Carmen Blanco-Gandia; M. Carmen Arenas; María A. Aguilar; Adrián Bartoll-Andrés; Olga Valverde; José Miñarro; Jorge Manzanares (Psychopharmacology, 2015)

Mucormycosis in a Non-Hodgkin Lymphoma Patient Caused by Syncephalastrum racemosum: Case Report and Review of Literature - Georgina Rodríguez-Gutiérrez; Erika M. Carrillo-Casas; Roberto Arenas; Jorge O. García-Méndez; Sonia Toussaint; Mónica E. Moreno-Morales; Adrián A. Schcolnik-Cabrera; Juan Xicohtencatl-Cortes; Rigoberto Hernández-Castro (Mycopathologia, 2015)

Ediacaran to Cambrian oceanic rocks of the Gondwana margin and their tectonic interpretation - Jürgen F. von Raumer; Gérard M. Stampfli; Ricardo Arenas; Sonia Sánchez Martínez (International Journal of Earth Sciences, 2015)

Combining physiological threshold knowledge to species distribution models is key to improving forecasts of the future niche for macroalgae - Brezo Martínez; Francisco Arenas; Alba Trilla; Rosa M. Viejo; Francisco Carreño (Global Change Biology, 2015)
Species distribution models ( SDM ) are a useful tool for predicting species range shifts in response to global warming. However, they do not explore the mechanisms underlying biological processes, making it difficult to predict shifts outside the environmental gradient where the model was trained. In this study, we combine correlative SDM s and knowledge on physiological limits to provide more robust predictions. The thermal thresholds obtained in growth and survival experiments were used as proxies of the fundamental niches of two foundational marine macrophytes. The geographic projections of these species’ distributions obtained using these thresholds and existing SDM s were similar in areas where the species are either absent‐rare or frequent and where their potential and realized niches match, reaching consensus predictions. The cold‐temperate foundational seaweed Himanthalia elongata was predicted to become extinct at its southern limit in northern Spain in response to global warming, whereas the occupancy of southern‐lusitanic Bifurcaria bifurcata was expected to increase. Combined approaches such as this one may also highlight geographic areas where models disagree potentially due to biotic factors. Physiological thresholds alone tended to over‐predict species prevalence, as they cannot identify absences in climatic conditions within the species’ range of physiological tolerance or at the optima. Although SDM s tended to have higher sensitivity than threshold models, they may include regressions that do not reflect causal mechanisms, constraining their predictive power. We present a simple example of how combining correlative and mechanistic knowledge provides a rapid way to gain insight into a species’ niche resulting in consistent predictions and highlighting potential sources of uncertainty in forecasted responses to climate change.

Higher sensitivity to the conditioned rewarding effects of cocaine and MDMA in High-Novelty-Seekers mice exposed to a cocaine binge during adolescence - A. Mateos-García; C. Roger-Sánchez; M. Rodriguez-Arias; J. Miñarro; M. A. Aguilar; C. Manzanedo; M. C. Arenas (Psychopharmacology, 2015)

The regime of climate-related disturbance and nutrient enrichment modulate macroalgal invasions in rockpools - Iacopo Bertocci; J. Domínguez Godino; C. Freitas; M. Incera; R. Araújo; A. Bio; F. Arenas; I. Sousa-Pinto; P. A. Reis; R. Domínguez (Biological Invasions, 2015)

B25716/1: a novel albumin-binding Gd-AAZTA MRI contrast agent with improved properties in tumor imaging - E. Gianolio; C. Cabella; S. Colombo Serra; G. Valbusa; F. Arena; A. Maiocchi; L. Miragoli; F. Tedoldi; F. Uggeri; M. Visigalli; P. Bardini; S. Aime (JBIC Journal of Biological Inorganic Chemistry, 2014)

Isolation of Pseudobutyrivibrio ruminis and Pseudobutyrivibrio xylanivorans from rumen of Creole goats fed native forage diet - D. J. Grilli; M. E. Cerón; S. Paez; V. Egea; L. Schnittger; S. Cravero; M. Sosa Escudero; L. Allegretti; G. N. Arenas (Folia Microbiologica, 2013)

Functional diversity and climate change: effects on the invasibility of macroalgal assemblages - F. Vaz-Pinto; C. Olabarria; I. Gestoso; E. Cacabelos; M. Incera; F. Arenas (Biological Invasions, 2013)

Physical factors driving intertidal macroalgae distribution: physiological stress of a dominant fucoid at its southern limit - Brezo Martínez; F. Arenas; M. Rubal; S. Burgués; R. Esteban; I. García-Plazaola; F. L. Figueroa; R. Pereira; L. Saldaña; I. Sousa-Pinto; A. Trilla; R. M. Viejo (Oecologia, 2012)

Reverse of the Decline of the Endangered Iberian Lynx - MIGUEL A SIMÓN; JOSÉ M. GIL‐SÁNCHEZ; GEMA RUIZ; GERMÁN GARROTE; EMIL B. MCCAIN; LEONARDO FERNÁNDEZ; MARCOS LÓPEZ‐PARRA; EVA ROJAS; RAFAEL ARENAS‐ROJAS; TERESA DEL REY; MARIBEL GARCÍA‐TARDÍO; GUILLERMO LÓPEZ (Conservation Biology, 2012)

The ecological importance of wetlands for aerial insectivores (swifts, martins and swallows) along the Tyrrhenian coast - Silvia Arena; Corrado Battisti; Giuseppe M. Carpaneto (Rendiconti Lincei. Scienze Fisiche e Naturali, 2011)

Harmonic amplitude-terms mask to highlight agriculture in the savanna domain below the Brazilian Amazonian frontier - J. M. Arenas-Toledo; J. C. N. Epiphanio (International Journal of Remote Sensing, 2011)

Partial characterization of hepatopancreatic and extracellular digestive proteinases of wild and cultivated Octopus maya - R. Martínez; R. Sántos; A. Álvarez; G. Cuzón; L. Arena; M. Mascaró; C. Pascual; C. Rosas (Aquaculture International, 2011)

Factors controlling present-day tufa dynamics in the Monasterio de Piedra Natural Park (Iberian Range, Spain): depositional environmental settings, sedimentation rates and hydrochemistry - M. Vázquez-Urbez; C. Arenas; C. Sancho; C. Osácar; L. Auqué; G. Pardo (International Journal of Earth Sciences, 2010)

Volatile exposure within the honeybee hive and its effect on olfactory discrimination - Vanesa M. Fernández; Andrés Arenas; Walter M. Farina (Journal of Comparative Physiology A, 2009)

Does pollen function as a reward for honeybees in associative learning? - C. Grüter; A. Arenas; W. M. Farina (Insectes Sociaux, 2008)

Age and rearing environment interact in the retention of early olfactory memories in honeybees - Andrés Arenas; Walter M. Farina (Journal of Comparative Physiology A, 2008)

Involvement of the ABC transporter BcAtrB and the laccase BcLCC2 in defence of Botrytis cinerea against the broad‐spectrum antibiotic 2,4‐diacetylphloroglucinol - Alexander Schouten; Olesya Maksimova; Yaite Cuesta‐Arenas; Grardy Van Den Berg; Jos M. Raaijmakers (Environmental Microbiology, 2008)
Summary The genetic and biochemical basis of defence mechanisms in plant pathogenic fungi against antifungal compounds produced by antagonistic microorganisms is largely unknown. The results of this study show that both degradative and non‐degradative defence mechanisms enable the plant pathogenic fungus Botrytis cinerea to resist the broad‐spectrum, phenolic antibiotic 2,4‐diacetylphloroglucinol (2,4‐DAPG). The efflux pump BcAtrB provides the first line of defence for B. cinerea , preventing accumulation of 2,4‐DAPG in the cell to toxic concentrations, whereas the extracellular laccase BcLCC2 mediates, via conversion of tannic acid, subsequent degradation of 2,4‐DAPG. Expression of BcatrB is induced by 2,4‐DAPG and efflux gives B. cinerea sufficient time to more effectively initiate the process of BcLCC2‐mediated antibiotic degradation. This is supported by the observations that the BcatrB mutant is significantly more sensitive to 2,4‐DAPG than its parental strain, and is substantially less effective in 2,4‐DAPG degradation. The results of this study further showed that BcLCC2 itself is not able to degrade 2,4‐DAPG, but requires tannic acid as a mediator for 2,4‐DAPG degradation. To our knowledge, this is the first time that the laccase‐mediator system is shown to play a role in the detoxification of a broad‐spectrum antibiotic compound from bacterial origin. We postulate that yet unknown constituents present in tannic acid act as substrate(s) of BcLCC2, thereby generating radicals that mediate 2,4‐DAPG degradation.

The effect of an anti-inflammatory pentapeptide produced by Entamoeba histolytica on gene expression in the U-937 monocytic cell line - R. Silva-García; I. Estrada-García; R. Ramos-Payán; A. Torres-Salazar; M. E. Morales-Martínez; D. Arenas-Aranda; J. A. Giménez-Scherer; F. Blanco-Favela; M. G. Rico-Rosillo (Inflammation Research, 2008)

Characterization of a Lactobacillus plantarum Strain Able to Produce Tyramine and Partial Cloning of a Putative Tyrosine Decarboxylase Gene - M. E. Arena; D. Fiocco; M. C. Manca de Nadra; I. Pardo; G. Spano (Current Microbiology, 2007)

Role of polyamines during in vitro rhizogenesis of Nothofagus nervosa using successive culture media - G. Martínez Pastur; M. E. Arena; M. P. Benavides; E. Eliasco; N. Curvetto (New Forests, 2007)

Floral odor learning within the hive affects honeybees’ foraging decisions - Andrés Arenas; Vanesa M. Fernández; Walter M. Farina (The Science of Nature, 2007)

Nestin, a neuroectodermal stem cell marker molecule, is expressed in Leydig cells of the human testis and in some specific cell types from human testicular tumours - Maria V. T. Lobo; Maria I. Arenas; F. Javier M. Alonso; Gonzalo Gomez; Eulalia Bazn; Carlos L. Pano; Eldiberto Fernndez; Benito Fraile; Ricardo Paniagua; Alfredo Moyano; Enrique Caso (Cell and Tissue Research, 2004)

An Imported Case of Blastomyces Dermatitidis Infection in Mexico - Roberto Velázquez; B. Muñoz-Hernández; R. Arenas; M. L. Taylor; F. Hernández-Hernández; M. E. Manjarrez; R. López-Martínez (Mycopathologia, 2003)

Successive media to improve the in vitro rhizogenesis of Nothofagus nervosa (Phil.) Dim. et Mil. - G. Martínez Pastur; M. Arena; N. Curvetto; D. Zappacosta; E. Eliasco (New Forests, 2003)

Biological Effects of Gestational and Lactational PCB Exposure in Neonatal and Juvenile C57BL/6 Mice - S. M. Arena; E. H. Greeley; R. S. Halbrook; L. G. Hansen; M. Segre (Archives of Environmental Contamination and Toxicology, 2003)

Effect of melatonin on hyperlipidemic nephropathy under constant light exposure - I. Túnez; M. C. Muñoz; M. Feijoo-López; E. Valdelvira; I. Bujalance-Arenas; P. Montilla (Journal of Physiology and Biochemistry, 2002)

Predicting Starling Chick Carcass PCB Concentrations from PCB Concentrations in Ingested Animal Matter - S. M. Arena; R. S. Halbrook; C. A. Arenal (Archives of Environmental Contamination and Toxicology, 1999)

Immunocytochemical and quantitative study of the tunica albuginea testis in young and ageing men - M. Isabel Arenas; Fermín R. Bethencourt; Benito Fraile; R. Paniagua (Histochemistry and Cell Biology, 1997)